Legal Review Of The Application Of Electronic Land Ownership Certificates In The Indonesian Legal System - Yusna Wulan Sari (Fakultas Hukum Dehasen, 2024)
In modern times such as today with the advancement of technology that is very rapidly growing, many things can be used to facilitate work such as in terms of community services, for example with the existence of e-land. The type of research used in this research is normative legal research (doctrinal legal research). The approach method in this study uses a statutory approach, an approach using legislation and regulations. The research results show that the implementation of electronic certificates is effective. Influential factors are human resources, facilities and infrastructure and quality of electronic data. Author Hopely: Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) as an electronic service provider in the land sector, maximize the use of electronic services, and more professional human resources, and improve data quality control so that results are maximized.